MESIN PENCACAH PLASTIK (PLASTIC SHREDDER) - Rezki, Miftahul; Ridwan, Muh.; Susanty, Asty Dewi; Rahmayana, Rahmayana; Ulfa, Sri; Muhammad H, Fadhil; Arya Apriansyah, Arya Apriansyah; Fathir, Lukman; Agustin, Mulfi Jumliah; Ilham, Ilham; Piter, Herwin; Ismirawati, Nur (Community Services and Social Work Bulletin, 2021)
Plastic type material is a material that is often used by many people in everyday life, the use of plastic materials, especially working in the world of health, industry or household, many people make plastic materials such as glass, plates, and more used as the necessities of everyday life. The sheer amount of plastic use has the potential to increase Polluttion and it is also very bad for the environment, mostly plastic materials are dumped without further processing, to reduce the impact of plastic materials needed for chopping tools to reduce the accumulation process. Using an AC motor as a drive system for chopping the plastic can make the plastic into a smaller part.